The existence of Kuda Lumping and Bantengan arts amidst technological developments - laila, ikrimah (Maliki Interdisciplinary Journal, 2024)
Kuda lumping is a native Indonesian cultural art located in East Java in the city of Ponorogo. It is an art that is very old, but this art continues to develop until modern times. Usually the lumping horse accompanies the reog which is performing, then the lumping horse dances compactly beside the reog. Then there is also something called bullan art, which also includes arts such as reog and also developed in Indonesia, especially in East Java, in the form of a bull made from large wood and then carved to resemble a bull's head. Bullan art developed in Mojokerto, Malang, Batu. It is true that this art has been around for a very long time, starting from the time when our ancestors existed, but even now in this modern era, whose life cannot be separated from technology, this art still survives and continues to be preserved, not only the old, young and even small children. loves this art.